PEEK -TiO2 composites with enhanced UV resistance. (20th October 2020) - Bragaglia, M.; Cherubini, V.; Nanni, F.
Abstract: In the paper, extruded filaments of polyetheretherketone (PEEK) filled (1%v, 3%v, 5%v) with sub-micrometric titanium dioxide (TiO2 ) particles have been manufactured with the aim to increase the UV radiation resistance of PEEK matrix. The TiO2 particles affect crystallinity of PEEK matrix as it increases increasing filler content. The filler presence slightly increases the stiffness and the elastic modulus of resulting composites and does not influence largely the tensile strength but show an influence on the elongation at break enhancing a finger like failure mechanism ascribed to microcracks propagation and interspherulitc fracture. UV aging test showed the effectiveness of TiO2 particles in reducing the photo-degradation effect especially in 5%v filled sample resulting the most effective formulation. For this formulation, after UV aging the mechanical properties and the failure mechanism remains unchanged while the neat PEEK sample shows embrittlement and loss of ductility. Graphical abstract: Image 1